Opsoclonus‐myoclonus in Aicardi‐Goutières syndrome. (21st June 2021) - Alburaiky, Salam; Dale, Russell C; Crow, Yanick J; Jones, Hannah F; Wassmer, Evangeline; Melki, Isabelle; Boespflug‐Tanguy, Odile; Do Cao, Jeremy; Gras, Domitille; Sharpe, Cynthia
Abstract : Aicardi‐Goutières syndrome (AGS) is a rare genetic neuroinflammatory disorder caused by abnormal upregulation of type 1 interferon signalling. Opsoclonus‐myoclonus syndrome is a rare autoimmune phenotype demonstrating a disturbance in the humoral immune response mostly seen in the context of paraneoplastic or postinfectious states, although its pathophysiology is incompletely understood. We report the first three children described with AGS demonstrating transient opsoclonus and myoclonus after irritability and/or developmental regression, suggesting a pathological association. We describe the presentation, clinical features, progress, cerebrospinal fluid (CSF) inflammatory markers, electroencephalogram (EEG), and magnetic resonance imaging (MRI) findings in these children. Two patients had developmental regression but demonstrated a positive response to JAK1/2 inhibition clinically and on serial examination of CSF inflammatory markers. These findings suggest that AGS should be considered in children presenting with opsoclonus‐myoclonus, and that the association between AGS and opsoclonus‐myoclonus further supports the role of immune dysregulation as causal in the rare neurological phenomenon opsoclonus and myoclonus. What this paper adds There is a phenotypic association between opsoclonus‐myoclonus syndrome and Aicardi‐Goutières syndrome. There is clinical evidence of immune dysregulation in the pathogenesis of opsoclonus and myoclonus. What this paper adds: There is a phenotypic association between opsoclonus‐myoclonus syndrome and Aicardi‐Goutières syndrome. There is clinical evidence of immune dysregulation in the pathogenesis of opsoclonus and myoclonus.